Consumer Willingness to Use Digital Coupons: A Case of Karachi Market in Pakistan - Kazi Afaq Ahmed; Zainab Sarwar (Institute of Business Management, 2018)
The coupon concept since its emergency in 1887 in US as marketing tool has gained lot of popularity in US market and emerged as effective marketing tool in South Asian Market. Unlike Indian and US Markets, the uptake of coupons has been very slow in Pakistan. This study aimed to check consumer willingness to use mobile coupons in Pakistan revealed that the interest and usage of mobile applications is growing with each day. People are willing to convert from traditional to digital platforms, similar to what we have noticed in the secondary research. Hi-Tec HHD devices are expanding throughout along with the usage. This research showed that the people are fond of downloading free mobile apps, which are mainly social, and gaming apps and a very small portion of the audience downloads paid apps (high-end market). It has been analyzed that the 50% of the audience would like to download a paid coupons app, which offers buy one get one free but there is a small portion of the population who is willing to spend Rs.4500 on purchasing the coupons book like Vouch365. There is a great potential for a business in Pakistan for the companies like Entertain Asia to penetrate into the market.